Modulation of autophagy by miRNAs - Kim, Yunha (BMB Rep, 2015)
MicroRNAs (miRNAs) can regulate the expression of genes that are involved in multiple cellular pathways. However, their targets and mechanism of action associated with the autophagy pathway are not fully investigated yet. EWSR1 (EWS RNA-Binding Protein 1/Ewing Sarcoma Break Point Region 1) gene encodes a RNA/DNA binding protein that is ubiquitously expressed and plays roles in numerous cellular processes. Recently, our group has shown that EWSR1 deficiency leads to developmental failure and accelerated senescence via processing of miRNAs, but its role in the regulation of autophagy remains elusive. In this context, we further investigated and found that EWSR1 deficiency triggers the activation of the DROSHA-mediated microprocessor complex and increases the levels of miR125a and miR351, which directly target Uvrag. Interestingly, the miR125a- and miR351-targeted reduction of Uvrag led to the inhibition of autophagy in both ewsr1 knockout (KO) MEFs and ewsr1 KO mice. In summary, our study demonstrates that EWSR1 is associated with the posttranscriptional regulation of Uvrag via miRNA processing. The regulation of autophagy pathway in miRNAs-Uvrag-dependent manner provides a novel mechanism of EWSR1 deficiency-related cellular dysfunction. [BMB Reports 2015; 48(7): 371-372]